Overseas music in the soundscapes of the cerrado: the captivating Fado in the state of Goiás and in the Federal District, Brazil - Santos, Jean Carlos Vieira; Lopes Filho , Jovanir José; Leite, Jairo Alves (Revista Cerrados, 2023)
Wrapped in the webs of an urban geography, a memory, or a tradition, the unclear origins of Fado date back to the 19th century, to episodes experienced in the alleys of Lisbon or in the aristocratic halls, between marginal people and nobles. When Fado became an UNESCO Intangible Cultural Heritage of Humanity, this Portuguese sound art reached all continents, entering different landscapes and territories around the globe. As a sign of an internationalization process in time and space, this article reflects on the presence of Fado in cities of the Brazilian cerrado in the state of Goiás and the Federal District. Using the qualitative method, the investigated scientific publications in depth: Valente (2008), Barreira (2010), Boscarino Júnior (2010), Cantero (2011), Monteiro (2013), Nunes (2013), Ulhôa (2013), Santos (2020), Silvestre (2015). Theaters, venues, and restaurants are the foundations of the presence of this Portuguese musical genre in the cities studied, with emphasis on its developments in the metropolitan regions of Goiania and Brasilia.